Exosomal miR-320d derived from adipose tissue-derived MSCs inhibits apoptosis in cardiomyocytes with atrial fibrillation (AF) - Lina Liu; Haoran Zhang; Hongyu Mao; Xiaohong Li; Yamin Hu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
MicroRNAs (miRNAs) play a key role in various pathological processes like atrial fibrillation (AF), which is a common cardiac arrhythmia. Exosomes are essential information carrier in the intercellular communication. Therefore, this study aimed to investigate the effects of exosomal miR-320d on cardiomyocytes with AF and related mechanisms. To do this, AMSCs were transfected with miR-320d mimics, AMSCs-derived exosomes were co-cultured with cardiomyocytes with AF. MTT, TUNEL staining, flow cytometry, real-time PCR, western blots, and luciferase reporter assays were performed. The results revealed that miR-320d expression was decreased in AF cardiomyocytes. AF increased apoptosis and reduced cell viability in cardiomyocytes. By transfection with miR-320d mimics, the miR-320d level was increased in AMSCs, exosomes and cardiomyocytes, which reversed the effect of AF on cardiomyocytes. STAT3 was down-regulated in AF cardiomyocytes and was a direct target gene of miR-320d. Inhibition of STAT3 abolished the effect of modified exosomes in cardiomyocytes, causing decreased apoptosis and increased cell viability. Taken together, the results suggested that exosomal miR-320d was associated with AF cardiomyocytes apoptosis and cell viability and that the effect of miR-320d on cardiomyocytes is STAT3-dependent. Therefore, this study provides a novel understanding of the molecular basis of AF and provides insight into therapeutic strategies for AF.